2020
DOI: 10.1177/0013161x20913897
|View full text |Cite
|
Sign up to set email alerts
|

Leading Inclusive Schools: Principal Perceptions, Practices, and Challenges to Meaningful Change

Abstract: Background: For over 50 years, special education has been used as a tool to maintain racial segregation, particularly in schools located in low-income communities of color. This study utilized tenets found in disability critical race theory (DisCrit) and inclusive school leadership literature to examine the perceptions, practices, and challenges associated with meaningful change in inclusive schools. Purpose: The purpose of this article was to understand how six elementary school principals, identified as effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 92 publications
(121 reference statements)
1
49
0
7
Order By: Relevance
“…As part of such efforts, principals report communicating with multiple constituencies, welcome the expression of concerns and recognize teachers' efforts in support of inclusion. DeMatthews et al (2020b) found that some principals further advanced an inclusive vision by applying an intersectional lens to consider students' multiple identities (e.g. race, gender and ability immigration status) and how schooling practices could be inclusive and reaffirming to many identities.…”
Section: Us Special Education Law and Challenges To Inclusionmentioning
confidence: 99%
“…As part of such efforts, principals report communicating with multiple constituencies, welcome the expression of concerns and recognize teachers' efforts in support of inclusion. DeMatthews et al (2020b) found that some principals further advanced an inclusive vision by applying an intersectional lens to consider students' multiple identities (e.g. race, gender and ability immigration status) and how schooling practices could be inclusive and reaffirming to many identities.…”
Section: Us Special Education Law and Challenges To Inclusionmentioning
confidence: 99%
“…A social justice approach can be thought of as positionality, a set of analytical skills, and a disposition for positive transformation. Effective school leaders tend to work from a similar core set of behaviors that promote a vision, support professional growth, redesign effective systems, and manage the core mission of teaching and learning (DeMatthews et al 2020;Leithwood et al 2008). However, within these examples of effective leadership practices there are distinctions revealing how a social justice lens influences not only motivations and perspectives, but also the skills school leaders use to build systems and solve problems.…”
Section: Social Justice In Practicementioning
confidence: 99%
“…Improvements in teacher preparation and high-stakes accountability policies requiring SWDs to meet grade-level expectations have arguably contributed to an increase in access and outcomes, though achievement gaps have not narrowed in decades (Gilmour et al , 2019). Despite 45 years of progress, many schools continue to struggle to meet the diverse needs of SWDs, with efforts toward inclusion often stymied by challenges relating to organizational and professional capacity and school cultures that do not support the goals of inclusion (DeMatthews and Mawhinney, 2014; DeMatthews et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research has focused on the effective inclusive leadership practices of principals (DeMatthews, 2015; DeMatthews and Mawhinney, 2014; European Agency for Special Needs and Inclusive Education, 2018; Guzmán, 1997; Hoppey and McLeskey, 2013; Mayrowetz and Weinstein, 1999; Waldron et al , 2011). This research examines how principals establish a vision for inclusion, build professional capacity, facilitate high-quality learning experiences and redesign organizational features to support SWDs (Billingsley et al , 2018; DeMatthews et al , 2021). The complexity of establishing an effective inclusive school and the stubborn persistence of exclusionary practices means educators often require both technical knowledge to apply research-based approaches to instructing SWDs as well as a critical awareness of and willingness to undo socio-cultural forces that manifest as racism, ableism and other forms of discrimination (Annamma et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation